Changes in surgical training opportunities in Britain and South Africa. (January 2016) - Greensmith, Martin; Cho, Jun; Hargest, Rachel
Abstract: Introduction: There have been substantial changes in the provision of surgical services and in surgical training over the last twenty years. Consultants now have a much greater role in delivery of care, but concerns have been raised over surgical trainees' lack of experience, particularly with trauma and emergency cases. Methods: The logbooks of surgical trainees undertaking 6 month posts during 1992–3 and 2009–12 in both the United Kingdom (UK) and South Africa (RSA) were analysed. Results: There was a 50% reduction in total hours worked between the UK posts in 1992–3 and 2011–12. The trainee post in RSA 2009–10 completed 15% more hours than the equivalent UK trainee post. Elective cases predominated in both UK posts (70–83%) whilst in RSA the number of trauma cases was substantial (21–26%). The UK 2011/12 trainee was rarely the primary operator (30%) compared with all other training periods (72–82%). This was due to a combination of relatively less minor and more major elective surgical cases in the recent UK post compared with the historical UK post or either RSA post. Conclusion: RSA has consistently offered more exposure to emergency, and especially trauma, surgery than the UK as well as more opportunity to act as primary operator. Re-introduction of "minor operations" lists for junior surgical trainees, acceptance of the importance for trainees to act as the primary operator, maintenance of the traditional "firm" structure and support for trainees who wish to spend a period of time abroad may help to improve clinical training and experience for UK surgical trainees. Highlights: The British senior surgical SHO trainee has been reduced from primary operator to assistant over the last twenty years. South Africa consistently offers a higher proportion of emergency general surgery including exposure to trauma surgery. South Africa offers more opportunity for the senior SHO trainee to act as primary operator, especially for major procedures. Trauma patients are generally young and fit and therefore may be more suitable for training operations. Re-introduction of minor operation training lists and return to a surgical team firm structure may improve trainee experience.